(untitled) (Research, Society and Development, 2022)
The objective of this research was to investigate the association between the intake of cariogenic foods and the presence of dental caries in schoolchildren. A cross-sectional study was developed in a municipal school in Recôncavo da Bahia, where 167 children, aged 3 to 12 years, had their oral condition evaluated. Only parents/guardians of 66 children answered the questionnaire on socioeconomic and demographic characteristics and 40 answered the QFA. To evaluate the intake of sugary foods, the Food Frequency Questionnaire was used, and the presence of caries was evaluated using the CPO-D/ceo-d index. A questionnaire was applied to the caregivers to identify demographic and socioeconomic characteristics. The variables were submitted to bivariate analysis (Pearson’s chi-square test) with a 5% significance level. The mean age of children was 6.8 years, with a predominance of mixed race/color (48.6%) and male (51.5%). As for the caretakers, 58.4% studied up to high school, 63.5% had an income of up to 1 minimum wage, and 97% lived in rural areas. The mean of CPO-D/ceo-d was 3.26 Children with caries had higher consumption of sugary foods. Dental caries showed statistically significant association with intake of fruit sweets (p<0.022) and diet soda (p<0.044). It can be stated that the results found in this study show the high rate of dental caries and ingestion of cariogenic foods, as well as the precarious oral hygiene on the part of the schoolchildren. However, it should be noted that this study has limitations due to its small sample size, although the relationship between caries and the consumption of some foods rich in sugar was found.